The state of mobile learning supported by gamification and augmented reality in higher education institutions across three continents - Durão, Natércia (2020)
The pervasive digitization is now a reality for organizations and society at large. In the last decade, for example, smartphones have been gradually transforming their scope from just voice communications providers to powerful media and computing devices. This transformation has led to a growth in business initiatives, namely in the services provision throughmobile applications. In this context, higher education asanorganizationandpartofsociety is compelled to change its operant mode in general and in particular in the teaching‐learning process making it more digital and at the same time more motivating for students. The aim of this study is to investigate the perception that higher education professors in the area of technology, across Southern Europe, South America, and Asia have about the use of mobile technologies such as gamification and augmented reality and how they can be used to promote student’sengagementinsideandoutsideoftheclassroom.